Development of urban fringe land in Dhaka using the land pooling/readjustment technique - Yasmin, Masuda; Archer, Raymon W.; Amin, A.T.M. Nurul; Kammeier, Hans Detlef; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1988)
The eastern fringe of Dhaka is undergoing transformation from rural to urban land use and the potential for its continuing urban development has been identified in various reports and studies. But the responsible government agencies are constructing very little infrastructure in the eastern fringe and the the area is characterized by spontaneous develop ment which results haphazard and unplanned l and conversion. The land pooling technique has proved to be successful in Japan, Korea and Taiwan as a technique for achieving timely servicing and subdivision of urban fringe land to a good standard at no cost to the government as the costs are recovered out of the related land value increase. The present study therefore aims to demonstrate by designing a case study land pooling project that land pooling could be adopted in Dhaka to improve the development of urban fringe areas. A draft l and pooling scheme was prepared for 10 ha. of l and which comprised 81 land parcels with 72 landowners. This scheme included the subdivision layout plan together with the network infrastructure plans, cost estimates, financial plan, schedule of the landowners, their land and its value , plot reallocation plan, and an implementation schedule. The proposed land pooling project would be implemented in 18 months. The landowners would have to give up 21.94 percent of their land for the road network, open space, mosque , school and community centre and 11.21 percent of their land for sale to recover the project cost. The landowners would get 66.85 percent of their original area as serviced plots with a net land value gain of 112 percent of the original land value. Due to the incomplete information on the landowners , only 40 of the 72 landowners were surveyed, but 35 of them expressed their willingness to join the proposed pooling project. The case study land pooling scheme and its support by the majority of the landowners surveyed shows the benefits and the feasibility of introducing this technique as a means of improving urban land development in Dhaka.
A Thesis Submitted in Partial Fulfilment of the Requirements for t he Award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Land use, Urban -- Bangladesh -- Dhaka